Selective enzymatic esterification of lignin model compounds in the ball mill - Weißbach, Ulla; Dabral, Saumya; Konnert, Laure; Bolm, Carsten; Hernández, José G. (Beilstein Journal of Organic Chemistry, 2017)
A lipase-catalyzed esterification of lignin model compounds in the ball mill was developed combining the advantages of enzyme catalysis and mechanochemistry. Under the described conditions, the primary aliphatic hydroxy groups present in the substrates were selectively modified by the biocatalyst to afford monoesterified products. Amongst the tested lipases, CALB proved to be the most effective biocatalyst for these transformations. Noteworthy, various acyl donors of different chain lengths were tolerated under the mechanochemical conditions.
Keywords: ball milling; enzymes; esterification; lignin derivatization; mechanochemistry